Serum Homocysteine Level in Type 2 Diabetes Mellitus with Peripheral Arterial Disease - Howlader, H; Ahmed, S; Sultana, N; Hasan, Z; Sadia, U; Ferdousi, S (Bangladesh Journal of Medical Biochemistry, 2013)
Peripheral arterial disease is a macrovascular complication of type 2 diabetes mellitus. Hyper-homocysteinemia is found to be associated with peripheral arterial disease. Homocysteine induced endothelial-cell injury is mediated by hydrogen peroxide. Hydrogen peroxide exposes the underlying matrix and smooth muscle cells of the arteries which, in turn, proliferate and promote the activation of platelets and leukocytes. The present study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2010 to June 2011 to observe the association of hyperhomocysteinemia with peripheral arterial disease in type 2 diabetes mellitus. A total of 100 subjects (50 cases and 50 controls) were selected by purposive sampling from Bangladesh Institute of Health sciences (BIHS) and BIRDEM Hospital, Dhaka. Subjects having ankle brachial index <0.9 were considered as cases and those having ankle brachial index 0.9 were considered as controls. Subjects with absent peripheral pulses or nonrecordable ankle brachial index were considered as ankle brachial index <0.9. All study subjects were normotensive, normolipidemic and non- smoker. The study showed a higher level of homocysteine (?mol/L) in cases when compared with that of controls (15.95±1.80 vs. 9.31±2.11; p<0.001). In cases, males had higher proportion of arterial disease (56%) than females. Other variables (age and body mass index) showed no significant difference between two groups. DOI: http://dx.doi.org/10.3329/bjmb.v6i1.13282 Bangladesh J Med Biochem 2013; 6(1): 14-18